Experience with enoxaparin in patients with mechanical heart valves who must withhold acenocumarol. Issue 5 (1st May 2003) - Ferreira, I; Dos, L; Tornos, P; Nicolau, I; Permanyer-Miralda, G; Soler-Soler, J
Abstract : Objectives: To evaluate the incidence of thromboembolic and haemorrhagic events in a cohort of patients with mechanical heart valves who had to withhold acenocumarol and were treated with enoxaparin. Design: Observational prospective study. Setting: In hospital; after discharge, and follow up by telephone call. Patients and methods: All consecutive patients with mechanical heart valves admitted to the authors' hospital between May 1999 and January 2002 who had to interrupt treatment with acenocumarol and were treated with enoxaparin as an alternative to other methods were enrolled. In each patient, the following characteristics were prospectively determined: the reason for interrupting acenocumarol, demographic data, estimated global risk for thromboembolic events, international normalised ratio before starting enoxaparin treatment, number of days taking enoxaparin, and mean level of anti-Xa activity during treatment. All patients were followed up through clinical history during the hospitalisation and by telephone after discharge to detect thromboembolic events. Main outcome measure: Presence of thromboembolic or haemorrhagic events. Results: 82 patients were identified and followed up for a mean of 2.8 months (range 1.5–3.5 months) after discharge. 61 of them (74%) had one or more associated thromboembolic risk factors. Acenocumarol was interrupted (to perform an invasive procedure in 74 patients and because of haemorrhagic complication in 8) an average of 11.2 days (range 3–40 days). Most patients received the standard enoxaparin dose (1 mg/kg at 12 hour intervals). Mean (SD) anti-Xa activity was 0.58 (0.3) IU/ml (median 0.51). There were 8 minor and 1 major bleeding events during enoxaparin treatment. No thromboembolic complications were clinically detected during hospitalisation or during follow up (95% confidence interval 0% to 3.6%). Conclusions: Enoxaparin may be an effective and relatively safe substitute anticoagulant for patients with mechanical heart valves who must withhold acenocumarol.